Biological activities and chemical characterization of Lavandula angustifolia essential oil from Seraïdi, Northeastern Algeria - ABDEL HAKIM HADJ MOUSSA; FOUZIA BENALIOUCHE; IBTISSEM SBARTAI; HANA SBARTAI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hadj Moussa AH, Benaliouche F, Sbartai I, Sbartai H. 2023. Biological activities and chemical characterization of Lavandula angustifolia essential oil from Seraïdi, Northeastern Algeria. Biodiversitas 24: 4535-4543. The objectives of this study are to examine the chemical composition of essential oil (EO) extracted by hydrodistillation from the flowering tops of dry lavender (Lavandula angustifolia) harvested in the town of Seraïdi in Northeastern Algeria and evaluate its antifungal, antibacterial, and antioxidant potential. The chemical analysis of this essential oil was carried out by gas chromatography coupled with mass spectrophotometry (GC-MS). The antimicrobial activity was evaluated by dilution method in solid and liquid medium, and the antioxidant activity was carried out using the DPPH° radical scavenging assay. It revealed the presence of 20 compounds representing the general component of this oil with a yield of 1.71%. This oil is composed mainly of Linalool (31.27%), followed by Camphor (16.21%), Linalool Oxide (11.98%), and Linalyl Acetate (11.93%). Other constituents were identified at relatively medium [2-Furarmethanol (7.49%), 1,8-Cineole/eucalyptol (6.76%), Borneol (5.34%)] and low contents [1-Hexyl butyrate (1.25%)]. The minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) of lavender EO against Fusarium roseum were 3000 µg/mL and 4000 µg/mL, respectively. Lavender OE had moderate antibacterial activity against Pseudomonas savastanoi. The antioxidant activity of lavender EO was lower than that of vitamin C.